THE EFFECT OF SERVICE QUALITY ON THE SATISFACTION OF MEDIA PARTNERS AT PT. MAIN SOLO AUDIO RADIO (SOLOPOS RADIO) - Cahyasari, Devi; Noriska, Ni Komang Septia (Jurnal Manajemen Bisnis dan Terapan, 2024)
Currently, many companies are opening services. This makes the level of competition of companies very tight. Therefore, these problems need to be considered by companies so that their business continuity is maintained. This study aims to analyze the quality of service on the satisfaction of media partners at Radio Solopos. In this study, a quantitative descriptive method is used. The respondents in this study are media partners of Radio Solopos. Of the 45 questionnaires distributed, the researcher took 30 respondents. Data collection was carried out by distributing questionnaires to respondents. The researcher calculated the questionnaire result using Social Science Statistics Package (SPSS) version 29 program. The result of this study is that service quality has a significant effect on media partner satisfaction. Because t counts are greater than t tables (7,254 > 2,048). So that if the quality of the service provided is high, then the higher the satisfaction that will be obtained by media colleagues. Radio Solopos needs to improve the quality of services provided and also evaluate the job desks of each division.